Preparation and luminescence properties of rare earth doped nanostructured zinc oxide thin films by sol gel technique - Aziz, Madzlan (American Institute of Physics, 2009)
Zinc oxide is a semiconductor cosidered promising for optoelectronic and solar cell applications. The wide bandgap nature of the zinc oxide has been a limitation in producing devices. Doping has been considered as one of the ways to reduce the band gap. In the present studies rare earth ions in the form of terbium and erbium nitatres have been introduced in the zinc oxide structure by the sol gel technique. Homogeneous thin film of nanostructured oxide and the doped homologue of the size range 30 to 80 nm were produced as characterized by scanning electron microscopy. The luminescence properties were investigated and the doped samples showed enhanced results. The enhancement were characterized as the extra energy levels produced by the dopants allowing more transitions to the lower states to take place. The dominant transitions were attributed to the 5D4 to 7FJ (J = 6 - 3) for the terbium doped systems and (4F7/2) to the ground state (4I15/2) for the erbium systems.